Characterizing the historical role of parenteral antischistosomal therapy in hepatitis C virus transmission in Egypt. (1st May 2020) - Ayoub, Houssein H; Chemaitelly, Hiam; Kouyoumjian, Silva P; Abu-Raddad, Laith J
Abstract: Background: Egypt is the nation most affected by hepatitis C virus (HCV) infection, following an epidemic of historic proportions. We aimed to characterize the epidemic's historical evolution and to delineate the role of parenteral antischistosomal therapy (PAT) campaigns in transmission. Methods: A mathematical model was constructed and analysed in order to understand HCV-transmission dynamics. The model was fitted to Egypt's Demographic and Health Survey data and to a systematic database of HCV-prevalence data. Results: The incidence rate peaked in 1966 at 15.7 infections per 1000 person-years—a period of time that coincides with the PAT campaigns—and rapidly declined thereafter, beginning the mid-1990s. The annual number of new infections peaked in 1993 at 581 200 (with rapid demographic growth), leading to a high-incidence-cohort effect, and declined to 67 800 by 2018. The number of individuals ever infected (1950–2018) was 16.4 million, with HCV prevalence peaking in 1979. The number of individuals ever exposed to PAT was 8.3 million; however, of these individuals, 7.3 million were alive in 1980 and only 3.5 million alive in 2018. The number of individuals ever infected due to PAT exposure was 963 900, with 850 200 individuals alive in 1980 and only 389 800 alive in 2018. The proportion of PAT-attributed prevalent infections peaked at 19.9% in 1972, declining to 5.5% by 2018. Conclusions: PAT campaigns played an important role in HCV transmission, yet explain only 6% of infections—they appear to be a manifestation, rather than a cause, of the epidemic. A possible driver of the epidemic could be the mass expansion of inadequate-quality healthcare during PAT campaigns and subsequent decades. Despite a historic toll, the epidemic has been rapidly diminishing since the mid-1990s.